Relations Between the Athletic Department and Sports Clubs in Albania. the Research in the Department of Athletics - Isufi, Madrit (European Journal of Multidisciplinary Studies, 2016)
“Athletics teaches lessons valuable to the individual by stretching the human spirit in ways that nothing else can” (Bowen - Levin, 2003, p. 243). In Albania there is a great andikap in the field of athletics. University knowledge related to this field remains at the level of undergraduate banks materialize in practice. Athletic Department is not an agreement with the clubs that train athletes or sports clubs for football are that the atletikor preparers often include as an assistant coach. Finally there is an initiative of the Ministry of Education and Sports to establish such cooperation and relations to make this part of plans and curricula, but it still has not been realized in practice, because Albania has an acute shortage of infrastructure. International Athletics Federation signed a memorandum of understanding with the Albanian Federation of Athletics. The aim was to help with programs for children, education of coaches and support initiatives for athletics at competitive levels. Also to support initiatives to better structure sportive. But that relations remained on paper, today manufactures athletic department student and prepare new trainers but without a vision for the space you created them employment, there is a vision for it, no one strategy and what is the most important projects there is cooperation with other countries to support athletic clubs and strengthen the work of professors athletic field with trainers. This study is important in helping gain an understanding of the relationship between coaches’ trust and how he or she perceives the athletic-director’s mindfulness within the athletic department. Lumpkin and Favor (2012) stated that “proponents of high school sport programs believe athletics contribute to the overall education of students” (p. 41). Sports play an important role in the Albanian society. Although high school sports are popular, more importantly many believe they are avenues for providing opportunities for justice, fair play, and teamwork. Sports and athletics express many of the cultural beliefs held by society, including the Protestant work ethic, capitalism, the bureaucratic mentality, and the ideals of fairness, teamwork, and sportsmanship, all of which are associated with collectivism (Beyer - Hannah, 2000).